Do the implementation processes of a school-based daily physical activity (DPA) program vary according to the socioeconomic context of the schools? a realist evaluation of the Active at school program - Véronique Gosselin; Suzanne Laberge (BMC, 2022)
Abstract Background Less than half of Canadian children meet the Canadian Physical Activity (PA) Guidelines, and the proportion is even lower among children living in underprivileged neighbourhoods. Regular PA supports physical, cognitive, and psychological/social health among school-aged children. Successful implementation of school-based daily physical activity (DPA) programs is therefore important for all children and crucial for children who attend schools in lower socioeconomic settings. The purpose of this study is to uncover what worked, for whom, how, and why during the three-year implementation period of a new "flexible" DPA program, while paying particular attention to the socioeconomic setting of the participating schools. Methods This study is a realist evaluation using mixed methods for data generation. Longitudinal data were collected in 415 schools once a year during the three-year implementation period of the program using questionnaires. Data analysis was completed in three steps and included qualitative thematic analysis using a mixed inductive and deductive method and chi-square tests to test and refine context-mechanism-outcome (CMO) configurations. Results Giving the school teams autonomy in the choice of strategies appropriate to their context have allowed schools to take ownership of program implementation by activating a community empowerment process, which resulted in a cultural shift towards a sustainable DPA provision in most settings. In rural underprivileged settings, the mobilization of local resources seems to have successfully created the conditions necessary for implementing and maintaining changes in practice. In disadvantaged urban settings, implementing local leadership structures (leader, committee, and meetings) provided pivotal assistance to members of the school teams in providing new DPA opportunities. However, without continued external funding, those schools seem unable to support local leadership structures on their own, jeopardizing the sustainability of the program for children living in disadvantaged urban areas. Conclusion By exploring CMO configurations, we have been able to better understand what worked, for whom, how and why during the three-year implementation period of the Active at School! program. When implementing DPA policies, decision makers should consider adjusting resource allocations to meet the actual needs of schools from different backgrounds to promote equal PA opportunities for all children.